Total quality management in education - Mukhopadhyay, Marmar (SAGE, 2020)
This is a completely revised new edition of a very successful text first published in 2001. The author combines extensive literature review with his own experience as institution builder, and his experiments on quality management to develop a practical guide for quality improvement for the education-institutional leaders.